If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -6(2x + -7) = -23 Reorder the terms: 8x + -6(-7 + 2x) = -23 8x + (-7 * -6 + 2x * -6) = -23 8x + (42 + -12x) = -23 Reorder the terms: 42 + 8x + -12x = -23 Combine like terms: 8x + -12x = -4x 42 + -4x = -23 Solving 42 + -4x = -23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + -4x = -23 + -42 Combine like terms: 42 + -42 = 0 0 + -4x = -23 + -42 -4x = -23 + -42 Combine like terms: -23 + -42 = -65 -4x = -65 Divide each side by '-4'. x = 16.25 Simplifying x = 16.25
| 8m+6n-3m+7n= | | -b^2+2b-6=0 | | 4y=7x^2-5 | | 4(2x+5)-7(x-3)= | | 8s-19=-25+6s | | 8(9+y)=7(y-3) | | sin(i)=0.4 | | 3t-3=-12+2t | | 2+2r=3-4r | | 3(n+4)=n+4 | | 14x+69=x | | 5z+3z=6z-7 | | x^3-4x^2-207x+630=0 | | 5x=88 | | 5x+2y+2z=7 | | 4(4x-8)-5=(x-3)+35 | | r+9.3=-0.5 | | (X+1)+(3x+1)+(x+1)=180 | | P(x)=-0.1x^5+3.8x^4+5000 | | 7-x=-2x-5 | | 0.4+1.5=2.2-15x | | 2n^2+2n-42=0 | | 5(3+5x)-1=89 | | 10-2a+4=32 | | 3=-4n+3n | | 2(j-3)=9(6-3j)+10j | | 9x^2+26x+17=0 | | 3p+6=2p+10 | | 20(y+2)=4y+5 | | 2j-6=54-27j+10j | | x-34=-14 | | 4X-30+X+20=180 |